Labour Policies of the Centre Right in the Neoliberal Era: The True Path Party - Caner Yacan (Siyasal: Journal of Political Sciences)
This study examines the labour policies of the True Path Party (TPP) to better understand the centre-right’s role in establishing neoliberalism in Turkey. Using a historical-comparative method, the article reveals significant changes in the Party’s labour policies from its establishment in 1983 to Süleyman Demirel’s Presidency (1983-1993). It is thought that a comparative examination of the period from the establishment of the Party to Demirel’s Presidency can reveal the dilemmas and continuities experienced in the Party’s labour policies depending on the neoliberal perspective. The TPP produced discourses aimed at gaining the support of labour immediately after its establishment in opposition to the structural conditions of the labour market in which it was born. These discourses expressed by the TPP are objections to the suppression of wage income, which is the most important element that ensures the sustainability of the accumulation process during the military rule (1980-1983) and the first civilian government following it and led by the Motherland Party. After becoming the head of the TPP (1987), Demirel brought to the fore the large inequalities in income distribution, argued for an effective labour market regulation to create full employment, and emphasised the relationship between poverty, wealth, and income distribution, which policymakers refrained from mentioning in the neoliberal process. However, during the Party’s rule, it lost the support of many worker organisations, especially unions affiliated with Türk-Iş.